1995
DOI: 10.1523/jneurosci.15-07-04906.1995
|View full text |Cite
|
Sign up to set email alerts
|

Cellular localization of synaptotagmin I, II, and III mRNAs in the central nervous system and pituitary and adrenal glands of the rat

Abstract: Three isoforms of synaptotagmin, a synaptic vesicle protein involved in neurotransmitter release, have been characterized in the rat, although functional differences between these isoforms have not been reported. In situ hybridization was used to define the localization of synaptotagmin I, II, and III transcripts in the rat CNS and pituitary and adrenal glands. Each of the three synaptotagmin genes has a unique expression pattern. The synaptotagmin III gene is expressed in most neurons, but transcripts are muc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
84
1
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(100 citation statements)
references
References 25 publications
14
84
1
1
Order By: Relevance
“…In recent years, a group of protein components of the exocytotic machinery has been shown to be present in the rat anterior pituitary gland (Wendland & Scheller 1994, Marquéze et al 1995, Oho et al 1995, Redecker et al 1995, Aguado et al 1996, Jacobsson & Meister 1996. The amount and immunocytochemical location of all of these proteins shown in the present study agrees with previous reports.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In recent years, a group of protein components of the exocytotic machinery has been shown to be present in the rat anterior pituitary gland (Wendland & Scheller 1994, Marquéze et al 1995, Oho et al 1995, Redecker et al 1995, Aguado et al 1996, Jacobsson & Meister 1996. The amount and immunocytochemical location of all of these proteins shown in the present study agrees with previous reports.…”
Section: Discussionsupporting
confidence: 91%
“…However, a functional role for these proteins and their non-neuronal isoforms has been proposed in different endocrine cell types (Lang et al 1997, Morgan & Burgoyne 1997). These molecular components of the exocytotic machinery have also been identified in anterior pituitary cells (Wendland & Scheller 1994, Marquéze et al 1995, Oho et al 1995, Redecker et al 1995, Aguado et al 1996, Jacobsson & Meister 1996, Majó et al 1998. In adenohypophyseal cells, t-SNAREs are located at the plasma membrane, and protein components of neuronal secretory organelle membranes are located on hormone-containing secretory granules and synaptic-like microvesicles (SLMV) (Wendland & Scheller 1994, Aguado et al 1996, Jacobsson & Meister 1996, Majó et al 1998.…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemistry also showed that complexin 1 expression is reduced throughout CA1 in PGC-1␣ Ϫ/Ϫ mice (data not shown). These large reductions in synaptotagmin 2 and complexin 1 in hippocampus are consistent with the fact that, within the hippocampus, these transcripts are primarily expressed by GABAergic interneurons (Marquèze et al, 1995;Eastwood et al, 2000).…”
Section: Loss Of Pgc-1␣ Causes Reduced Levels Of Specific Synaptic Prsupporting
confidence: 58%
“…Second, recombinant expression of synaptotagmin revealed that synaptotagmin 2 can act as a fast Ca 2ϩ sensor and functionally replace synaptotagmin 1 (16). Finally, expression of synaptotagmin 2 mRNA and protein was previously demonstrated in scattered neurons in the hilus (20,33) and immunolabeling with the antibody znp-1 (presumably recognizing synaptotagmin 2) was found in presynaptic terminals located on somata of CA1 hippocampal pyramidal neurons (34).…”
Section: Discussionmentioning
confidence: 96%
“…The functional role of the other synaptotagmins has remained unclear. Synaptotagmins are differentially expressed in central neurons (16,19,20) and differ in kinetic properties (21). Thus, it is possible that differential expression of synaptotagmins determines the time course of transmitter release and the proportion of synchronous and asynchronous release at different synapses (6,(22)(23)(24).…”
mentioning
confidence: 99%